Peranan Media Kartu Arisan Fisika (KARSANFIS) Dalam Pembelajaran STAD Terhadap Hasil Belajar Fisika Siswa - Kholida, S. Ida; Suprianto, Suprianto; Amalia, Rica (Universitas Islam Madura, 2023)
The monotonous physics learning process causes students to lose interest in physics learning material. The aim of this study is to identify differences in the achievement of physics learning outcomes between students who utilize the physics social gathering card (KARSANFIS) media in the STAD learning context and those who do not utilize the media and to evaluate the significant impact of using the KARSANFIS media in STAD learning on learning outcomes. physics students. This study applied a quasi-experimental method carried out at MA Nurul Istiqlal, Pamekasan Regency, involving 40 students as research samples, consisting of two classes, namely classes X-1 and X-2. Data analysis involves normality tests, homogeneity tests, and t tests. The descriptive results of this study show that the posttest scores in the control group and the experimental group are 67.50 and 78.25. The t test results indicated that the posttest p-value was 0.014 (p-value < α= 0.05), while the anova test results for the difference between posttest and pretest scores had a p-value of 0.001 (p-value < α= 0.05). From these findings it can be concluded that the role of KARSANFIS media in STAD learning provides a significant difference in students' physics learning outcomes compared to those who do not use the media, and the use of KARSANFIS media in STAD learning is able to significantly influence the achievement of student learning outcomes. Keywords: STAD type cooperative learning, learning outcomes, physics arisan card media Abstrak: Proses pembelajaran Fisika yang monoton mengakibatkan siswa kehilangan minat dalam materi pembelajaran fisika. Tujuan dari studi ini adalah untuk mengidentifikasi perbedaan dalam pencapaian hasil belajar fisika antara siswa yang memanfaatkan media kartu arisan fisika (KARSANFIS) dalam konteks pembelajaran STAD dengan mereka yang tidak memanfaatkan media serta untuk mengevaluasi dampak yang signifikan dari pemanfaatan media KARSANFIS dalam pembelajaran STAD terhadap hasil belajar fisika siswa. Studi ini menerapkan metode eksperimen semu yang dilakukan di MA Nurul Istiqlal Kabupaten Pamekasan dengan melibatkan 40 siswa sebagai sampel penelitian, yang terdiri dari dua kelas, yaitu kelas X-1 dan X-2. Analisis data melibatkan uji normalitas, uji homogenitas, dan uji t. Hasil deskriptif dari penelitian ini menunjukkan bahwa skor posttest pada kelompok kontrol dan kelompok eksperimen adalah 67.50 dan 78.25. Hasil uji t mengindikasikan bahwa p-value posttest sebesar 0.014 (p-value < α= 0.05), sedangkan hasil uji anova untuk selisih nilai posttest dan pretest memilki p-value sebesar 0.001 (p-value < α= 0.05). Simpulan dalam studi ini adalah peranan media KARSANFIS memiliki dampak pada hasil belajar siswa yang berbeda secara signifikan dibandingkan dengan mereka yang tidak memanfaatkan media, serta pemanfaatan media KARSANFIS dalam pembelajaran STAD mampu mempengaruhi secara signifikan pencapaian hasil belajar siswa.